Psychosexual distress in women with gynecologic cancer: a feasibility study of an online support group. Issue 4 (28th February 2012) - Classen, Catherine C.; Chivers, Meredith L.; Urowitz, Sara; Barbera, Lisa; Wiljer, David; O'Rinn, Susan; Ferguson, Sarah E.
Abstract: Objectives: The psychosexual concerns of gynecologic cancer patients are often unaddressed and there are limited resources available for women to deal with this highly sensitive topic. This feasibility study examines the participation rates and preliminary outcomes for an online support group designed specifically for women who are sexually distressed subsequent to gynecologic cancer treatment Methods: A 12‐week online intervention was developed to address the psychosexual impact of gynecologic cancer. This intervention included a professionally moderated, asynchronous discussion forum as well as the provision of psycho‐educational materials addressing the psychosexual impact of gynecologic cancer. Each week, a new topic was introduced and relevant material was posted on the website. Women were encouraged to share their experiences related to the topic. Twenty‐seven, sexually distressed, remitted gynecologic cancer patients were randomly assigned to immediate treatment or a waitlist control condition. Participants completed questionnaires at baseline, 4‐month and 8‐month follow‐ups assessing sexual distress as the primary outcome as well as anxiety, depression, and illness intrusiveness. Results: Participation rates differed between the two groups, with greater participation occurring in the second group. Exit interviews indicated that the majority of the participants were satisfied with the intervention. Intent‐to‐treat analyses suggest a small effect for reduction in sexual distress Conclusions: This feasibility study suggests that women find this intervention acceptable. Further research is required to determine efficacy. Copyright © 2012 John Wiley & Sons, Ltd.